(untitled) (Indianapolis, IN, 2007)
This essential resource book offers a no-nonsense introduction to using the tools the way they were meant to be used. The authors walk you through the overall user interface of the Visual Studio Team Edition for Software Developers and Visual Studio Team Edition for Software Testers. You'll explore each of the available test types and learn how to effectively use the code analysis and dynamic analysis tools to quickly become effective as a software developer or test engineer.
Keywords: Computer software,Phần mềm máy tính; Testing,Kiểm tra